2003
DOI: 10.1021/jp030345e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Liquid Structure Relaxation from Criticality after a Nanosecond Laser Initiated T-Jump in Triethylamine−Water

Abstract: Due to its lower critical consolute temperature, we can use a nanosecond laser T-jump to induce spinodal demixing in the triethylamine/water binary mixture. Using a time-resolved Raman probe, we obtained direct molecular level evidence for liquid restructuring in the early stage (<200 ns) of this spinodal decomposition. From these Raman data, we concluded that in this system the early and intermediate stage spinodal dynamics were apparently over within 1 µs. In addition to Raman spectroscopy, we developed a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 59 publications
5
32
2
Order By: Relevance
“…Obtaining the difference between the spectrum before the T‐jump and after the T‐jump separates the useful, but relatively small, spectral changes from the main spectral information, allowing us to finely pinpoint and interpret the shifts due to the breaking of the TEA/H 2 O hydrogen‐bonded complex at hypercritical temperatures. As we have stressed, the spectral shifts and difference spectra obtained after the T‐jump were fully consistent with the spectral shifts observed in the two individual layers in a mixture of the same composition that had been phase split using a static temperature rise equal to the predicted laser‐induced rise 11.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Obtaining the difference between the spectrum before the T‐jump and after the T‐jump separates the useful, but relatively small, spectral changes from the main spectral information, allowing us to finely pinpoint and interpret the shifts due to the breaking of the TEA/H 2 O hydrogen‐bonded complex at hypercritical temperatures. As we have stressed, the spectral shifts and difference spectra obtained after the T‐jump were fully consistent with the spectral shifts observed in the two individual layers in a mixture of the same composition that had been phase split using a static temperature rise equal to the predicted laser‐induced rise 11.…”
Section: Introductionsupporting
confidence: 82%
“…In a recent study 11, we recently reported on phase change following a nanosecond laser‐induced temperature jump (T‐jump) in classic triethylamine–water (TEA/H 2 O) system 12. In that study, we introduced a sensitive Raman detection scheme that allows one more precisely and quantitatively determine ratio of solute molecules solvated with solvent molecules, and in particular, TEA with water in diluted solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] When we modify the specific system to be investigated, the spectra should change accordingly. If the change is pertinent to the system of our interest, the differential spectra could reveal more definite information on the system in question than the original spectra, by subtracting irrelevant spectral signals from other common parts.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the differential spectra is quite general as well. To just illustrate a few examples, the differential spectroscopy has been applied to investigate the hydrated protons in water, 3 dynamics of liquid-liquid phase separation, 4 ion adsorption and desolvation at electrodes, 5,6 ion channel of membranes, 7 etc. For example, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the firm evidence in support of speeding up that exists in the case of the reaction of 2-chloro-2-methylbutane in isobutyric acid + water (UCST) [12,13], the reaction of 2-bromo-2-methylpropane in triethylamine + water (LCST) [13], and the decomposition of acetone dicarboxylic acid in isobutyric acid + water (UCST) [15]. Speeding up also has been observed, for example, in the rate of dielectric relaxation in ethanol + dodecane (UCST) [24] and perhaps also in the rate of spinodal decomposition in triethylamine + water (UCST) [25].…”
Section: Discussionmentioning
confidence: 99%